TINGKAT KESEGARAN JASMANI SISWA KELAS V SD SEKEPENGHULUAN BUKIT SELAMAT KABUPATEN ROKAN HILIR - Dedek Kurniati Rahayu; Zainur Zainur; Aref Vai (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2021)
Abstract: The problem in this study is seen that most students who are not eager to follow the learning, some are limp, not concentrated, evaporate or sleepy in following the learning, resulting in a lack of maximum peroses of physical sports learning peroses from grade V students of SD Negeri 007 hill four and grade V students of SD Negeri 011 siderejo which is always no improvement. The purpose of this study was to find out the level of physical freshness of both schools. this research was carried out at SD Negeri 007 bukit empat and SD Negeri 011 siderejo kepenghuluan bukit sekamat rokan hilir district, the population in this study is 29 students and sampling using saturated sampling techniques, time in data collection in January samapai November 2020. This research uses descriptive quantitative method, the data in this study are physical freshness test data of students of SD Negeri 007 hill four and students of sd Negeri.Key Words: Level of Physical Freshness